2011
DOI: 10.1111/j.1523-1739.2011.01793.x
|View full text |Cite
|
Sign up to set email alerts
|

Northward Shifts of the Distributions of Spanish Reptiles in Association with Climate Change

Abstract: It is predicted that climate change will drive extinctions of some reptiles and that the number of these extinctions will depend on whether reptiles are able to change their distribution. Whether the latitudinal distribution of reptiles may change in response to increases in temperature is unknown. We used data on reptile distributions collected during the 20th century to analyze whether changes in the distributions of reptiles in Spain are associated with increases in temperature. We controlled for biases in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 43 publications
(49 reference statements)
3
55
0
2
Order By: Relevance
“…1; Table 1). These results agree with those of other studies (Moreno-Rueda et al 2011). Changes in other directions were also detected in our study, and agree with an increasing number of reports have documented other types of range shifts, such as east-west shifts across longitudes or even shifts toward tropical latitudes and lower elevations (Lenoir and Svenning 2015).…”
Section: Discussionsupporting
confidence: 96%
See 3 more Smart Citations
“…1; Table 1). These results agree with those of other studies (Moreno-Rueda et al 2011). Changes in other directions were also detected in our study, and agree with an increasing number of reports have documented other types of range shifts, such as east-west shifts across longitudes or even shifts toward tropical latitudes and lower elevations (Lenoir and Svenning 2015).…”
Section: Discussionsupporting
confidence: 96%
“…Some studies have found that the effects of previous temperature changes on the distribution of the reptiles are crucial (Moreno-Rueda et al 2011). In our study, shifts in the northern boundaries and distribution center coordinates for the majority of snake species mimicked the trends in C-J and C-W stand for the center longitude and latitude, respectively; S, N, W, and E stand for the southern boundary, northern boundary, western boundary, and eastern boundary, respectively temperature changes, whereas changes in the southern, western, or eastern boundaries of several species also shifted with increases in temperature-based factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SDMs are essential tools for both predicting the impacts of climatic change on biodiversity, and designing conservation plans and policies which best mitigate the effects of climate change [26]. Recent notable examples are by [19,20,[27][28][29][30][31][32][33]. However, it is recognized that there are significant limitations in projecting future species distribution using SDMs [34,35].…”
Section: Introductionmentioning
confidence: 99%